LEFT ATRIUM VOLUME AS A SURROGATE MARKER OF LEFT VENTRICULAR DIASTOLIC DYSFUNCTION - Hadi, Abdul; Iqbal, Muhammad Asif; Ahmad, Farooq; ., Ikramullah; Ashraf, Amber; ., Hafizurehman (Journal of Postgraduate Medical Institute, 2016)
Objective: To determine correlation between left atrial volume and left ven -tricular diastolic dysfunction. Methodology: This was a single center observational study conducted at Lady Reading Hospital, Peshawar. Patients above 18 years of both genders, who were in sinus rhythm and having no significant systolic dysfunction or significant mitral insufficiency on echocardiography, were included in the study, using purposive non-probability sampling technique. A total 339 pa -tients underwent transthoracic echocardiography from July 2013 to June 2014. Detailed cardiac echocardiography was performed to determine left atrial volume, ejection fraction, E and A velocities, deceleration time and e've-locity, E/e.' Results: A total of 339 patients were studied. Male were 61.9%. Mean age of study population was 58.42 ±10.48 years. Baseline characteristics of patients having some degree of diastolic dysfunction were; mean age 65.5 ±12.3, mean body mass index 25.2 ±2.5 kg/m2, mean ejection fraction 55.1 ±7.5%, hypertension 48.6%, diabetes mellitus 10.1% and left ventricular hypertrophy 38.6%. Echocardiographic findings in diastolic dysfunction patients were as follow: mean left atrial volume was 65.3 ±10.1ml, E/A 1.4 ±0.6, TDI e' was 6.7 ±1.3 m/sec and TDI E/e' was 12.7 ±2.1. Increasing left atrial volume was well correlated with increasing severity of left ventricular diastolic dysfunction (Î³ = +0.8, Spearman rank correlation). Conclusion: Increase in left atrial volume is directly correlated with severity of diastolic dysfunction. Severity of diastolic dysfunction increases with in-creased left atrial volume.